Keanekaragaman Perifiton Pada Daun Lamun Di Pantai Tukak Kabupaten Bangka Selatan - Wibowo, Ari; Umroh, Umroh; Rosalina, Dwi (AQUATIC, 2014)
Periphyton is one of organism of vegetation and animal that sticks on surface of seagrass leaves and associated with seagrass as host. Periphyton is one of component in waters productivity providers. The aims of this study are to determine the types of periphyton which sticks on the leaves of seagrass in Tukak Beach, to knowing the types of seagrass and to knowing the types ofÂ  seagrass which stuck on by periphyton. The research was conducted in May-August 2011 in Tukak Beach. The data retrieval consists of three stations, where at each station is divided into three substations, the data was taken including leaves of seagrass species and physical-chemical parameters of waters. The result of this study show that 5 species seagrass was identified which are Cymodocea rotundata, Cymodocea serrulata, Thalassia hemprichii, Enhalus acoroides dan Halodule uninervis. Periphyton was identified on seagrass leaves consisting of Fragilaria, Anabaenopsis, Diploneis, Synedra, Amphora, Nitzchia, Coleochaeta, Atractomorpha, Stylonema, Dasya, Spermothamnion and Acnanthes. Heterogenous value index (H) supreme on Thalassia hemprichii and Enhalus acoroides ranging among 2,42-2,46. Domination index (e) ranging among 0,97-0,99. Periphyton organism prefer the leaves of Thalassia hemprichii and Enhalus acoroides to stick and made as host , it cause Thalassia hemprichii and Enhalus acoroides has a width and length of leaf surface and considered condition of leaf was old.